PERILAKU CARING DAN KEPUASAN LAYANAN KEPERAWATAN DI RUANG RAWAT INAP BEDAH RSUD JENDERAL AHMAD YANI METRO - Anita; Wulan Kurniati; El Rahmayanti (Optimal Nursing Journal, 2026)
ABSTRACT Satisfaction in service is influenced by several factors, one of which is the caring attitude of nurses. The Ministry of Health of the Republic of Indonesia in 2016 set a minimum standard of patient satisfaction above 95%, whereas the phenomenon in Indonesia shows patient satisfaction rates of 42.8% in Central Maluku and 44.4% in West Sumatra (Latupono et al, 2014; Rangki, 2021). The most common patient complaints are nurses' attitudes and suboptimal services. The purpose of this study is to determine the relationship between caring behavior and satisfaction with nursing services in the surgical inpatient ward at RSUD Jenderal Ahmad Yani Metro in 2025. Methods: The study is quantitative with a cross-sectional approach. The sample consisted of 52 surgical nurses using purposive sampling. Instruments include a nursing service satisfaction questionnaire and a caring behavior observation sheet with a CDI 25. The statistical test used was the chi-square test. The results of this study showed that 33 respondents (63.5%) were satisfied with the nursing services and 38 nurse respondents (73.1%) provided nursing care services with caring behavior. The statistical test results obtained a p-value = 0.000 (p < 0.05), so it can be concluded that there is a relationship between caring behavior and satisfaction with nursing services in the surgical inpatient room at RSUD Jenderal Ahmad Yani Metro. Nurses can apply the caring concept to improve the quality of nursing care in the surgical inpatient room because this aspect greatly contributes to patient satisfaction. Keywords: Satisfaction, Nursing Services, Caring Behavior. References: 18 (2017-2024)